Option pricing with downward-sloping demand curves: The case of supply chain options - Burnetas, A; Ritchken, P (Management Science, 2005)
This article investigates the role of option contracts in a supply chain when the demand curve is downward sloping. We consider call (put) options that provide the retailer with the right to reorder (return) goods at a fixed price. We show that the introduction of option contracts causes the wholesale price to increase and the volatility of the retail price to decrease. In general, options are not zero-sum games. Conditions are derived under which the manufacturer prefers to use options. When this happens the retailer is also better off, if the uncertainty in the demand curve is low. However, if the uncertainty is sufficiently high, then the introduction of option contracts alters the equilibrium prices in a way that hurts the retailer. © 2005 INFORMS.
Keywords: Contracts; Downward-sloping demand curves; Industrial management; Inventory control; Marketing; Problem solving; Product design; Real options; Sales; Stackelberg games; Supply chain contracts